Laser manipulation of cells and tissues - Berns, Michael W.; Greulich, Karl Otto (Methods in cell biology, 2007)
The use of laser-based manipulation tools has literally exploded on the cell biology and molecular pathology scene, resulting in as many different laser micromanipulation systems as there are people using them. Laser Manipulation of Cells and Tissues ties all these systems and studies together, describing all of the different kinds of research and practical/analytical applications of laser manipulation. It also provides the reader with the basic information needed to actually build one’s own laser micro-manipulation system. The combination of imaging and molecular probe technology with laser micromanipulation greatly extends the use of this technology in molecular, cellular, developmental and patho-biology/medicine. This book should be valuable to scientists, clinicians, and students in the fields of cell and developmental biology, cell physiology, cancer biology, pathology, and stem cell biology.--Provided by publisher.